Factors influencing tax aggressiveness: profit management, leverage, and profitability - Siburian, Simon Agus; Kuntadi, Cris (Universitas Wiralodra, 2023)
Previous or relevant research is fundamental in a research or scientific article. Previous or relevant research strengthens the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence tax aggressiveness, earnings management, leverage, and profitability, a literature study on tax accounting. This article aims to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Profit Management influences Tax Aggressiveness; 2) Leverage affects Aggressiveness; and 3) Profitability affects Tax Aggressiveness.